2018
DOI: 10.15252/embr.201744445
|View full text |Cite
|
Sign up to set email alerts
|

MacroH2A histone variants limit chromatin plasticity through two distinct mechanisms

Abstract: MacroH2A histone variants suppress tumor progression and act as epigenetic barriers to induced pluripotency. How they impart their influence on chromatin plasticity is not well understood. Here, we analyze how the different domains of macroH2A proteins contribute to chromatin structure and dynamics. By solving the crystal structure of the macrodomain of human macroH2A2 at 1.7 Å, we find that its putative binding pocket exhibits marked structural differences compared with the macroH2A1.1 isoform, rendering macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 60 publications
7
56
0
Order By: Relevance
“…Furthermore, only macroH2A.1.1 suppresses PARP1 activity, preventing the formation of an open chromatin structure. By contrast, all three histone variants of macroH2A (macroH2A.1.1, macroH2A.1.2 and macroH2A.2) retain the ability to stabilise condensed chromatin structure via their common linker region [115]. Subsequently, macroH2A.1.1 participates in recognizing and binding PAR chains to inactivate PARP1 ( Figure 4C), whereas the linker region, being present in all three isoforms, may play an additional role in chromatin compaction.…”
Section: Parylation In the Regulation Of Dna Damage-induced Chromatinmentioning
confidence: 99%
“…Furthermore, only macroH2A.1.1 suppresses PARP1 activity, preventing the formation of an open chromatin structure. By contrast, all three histone variants of macroH2A (macroH2A.1.1, macroH2A.1.2 and macroH2A.2) retain the ability to stabilise condensed chromatin structure via their common linker region [115]. Subsequently, macroH2A.1.1 participates in recognizing and binding PAR chains to inactivate PARP1 ( Figure 4C), whereas the linker region, being present in all three isoforms, may play an additional role in chromatin compaction.…”
Section: Parylation In the Regulation Of Dna Damage-induced Chromatinmentioning
confidence: 99%
“…Interestingly, PARP1 and macroH2A1.2 have opposing effects on chromatin structure. PARP1 and PARylation decompacts chromatin while macroH2A1 compacts chromatin, including through a mechanism involving PAR binding by the macrodomain of macroH2A1.1 (Khurana et al, 2014;Kozlowski et al, 2018;Krishnakumar and Kraus, 2010;Timinszky et al, 2009). macroH2A1.2 lacks a PAR-binding macrodomain but recent evidence has shown that this variant is still able to compact chromatin through an activity located in the linker region (Kozlowski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the histone variant macroH2A as this variant can bind and be regulated by PARP and is involved in HR (Khurana et al, 2014;Ruiz et al, 2019;Timinszky et al, 2009). macroH2A1 has two splice variants, macroH2A1.1 and macroH2A1.2, which differ in 32 amino acids within the C-terminal macrodomain leading to the presence of a PAR binding domain in macroH2A1.1 but not in macroH2A1.2 (Kozlowski et al, 2018;Timinszky et al, 2009). macroH2A2 is expressed from a second, independent gene and does not bind to PAR but is ~80% identical with macroH2A1 (Posavec et al, 2013).…”
Section: Kdm5a Interacts With the Histone Variant Macroh2a1mentioning
confidence: 99%
“…In stickleback, we found multiple genes coding for H2A variants such as H2Afv, while only one gene codes for macroH2A that can give rise to three isoforms. This differs from mammals, where macroH2A was duplicated and gives rise to three isoforms (2 proteins gene 1, 1 protein gene 2) (Kozlowski et al, 2018). This, in conjunction with its duplication in a number of fish species, suggests potential teleost-specific biological functions.…”
Section: Stickleback H2amentioning
confidence: 91%
“…This, in conjunction with its duplication in a number of fish species, suggests potential teleost-specific biological functions. Furthermore, in our opinion, macroH2A might be of particular interest for eco-evolutionary studies as it has been linked to embryonic defects in mouse and zebrafish (Kozlowski et al, 2018), and is essential to cold acclimation in fish (Pinto et al, 2005).…”
Section: Stickleback H2amentioning
confidence: 96%